2016
DOI: 10.1007/s00382-016-3398-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an ensemble of ocean–atmosphere coupled and uncoupled regional climate models to reproduce the climatology of Mediterranean cyclones

Abstract: Aegean Seas, as well as in the areas close to Cyprus and to Atlas mountains. The RCMs tend to underestimate intense cyclone occurrences over the Mediterranean Sea and reproduce 24-40 % of these systems, as identified in the reanalysis. The use of grid nudging in one of the RCMs is shown to be beneficial, reproducing about 60 % of the intense cyclones and keeping a better track of the seasonal cycle of intense cyclogenesis. Finally, the most intense cyclones tend to be similarly reproduced in coupled and uncoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 87 publications
7
49
2
Order By: Relevance
“…WM Sea with contrasting cyclogenesis mechanisms in different seasons (Campins et al, 2010;Flaounas et al, 2018;Lionello et al, 2016;Trigo et al, 1999;Trigo et al, 2002). These regions are the Gulf of Genoa/Ligurian Sea and Northern Italy, the Adriatic Sea and Dinaric Alps, the Iberian Peninsula and North African Coast ( Figure 1 and Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…WM Sea with contrasting cyclogenesis mechanisms in different seasons (Campins et al, 2010;Flaounas et al, 2018;Lionello et al, 2016;Trigo et al, 1999;Trigo et al, 2002). These regions are the Gulf of Genoa/Ligurian Sea and Northern Italy, the Adriatic Sea and Dinaric Alps, the Iberian Peninsula and North African Coast ( Figure 1 and Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This study aims at analyzing the dynamics of the Adriatic‐Ionian‐Aegean Sea system using a multimodel approach. The advantages of using a multimodel approach in the Mediterranean region have been shown in the analysis of heat and salt budget (Harzallah et al, ; Llasses et al, ), but also in analysis of atmospheric circulation over the area (Flaounas et al, ). These studies have shown that a multimodel approach is able to describe the main features and mechanisms driving the atmosphere‐ocean circulation over the Mediterranean region (Ruti et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Each panel refers to a different coastal location (red square). It is evident that cyclone tracks initiate in the well-known cyclogenetic areas located inside and around the Mediterranean Sea (North Africa, south of the Atlas Mountains, Gulf of Genoa, Adriatic Sea, Cyprus area, Black Sea area) and in the northeastern Atlantic (H.M.S.O., 1962;Alpert et al, 1990;Trigo et al, 1999Trigo et al, , 2002Maheras et al, 2001;Lionello et al, 2002Lionello et al, , 2016Garcies and Homar, 2011;Nissen et al, 2010;Campins et al, 2011;Reale and Lionello, 2013). The prevalent motion of the cyclone centre is southeastwards along the Mediterranean branch of the Mediterranean storm track.…”
Section: Cyclone Tracks Associated With Large Sea Level Anomaliesmentioning
confidence: 99%
“…The MR is indeed characterised by a high frequency of cyclogenesis processes, in particular in areas such as the lee of the Alps and Atlas Mountains, the northern Aegean Sea, Cyprus area, the Black Sea, and the Iberian Peninsula. The presence of the Mediterranean branch of the Northern Hemisphere storm track is evident in the results of cyclone tracking methods (Lionello et al, 2016;Flaounas et al, 2016) and it has been extensively studied in the scientific literature (H.M.S.O., 1962;Alpert et al, 1990;Trigo et al, 1999; Figure 1. The Mediterranean region with the coastal stations considered in this study (starting from the west in clockwise direction along the coastline): Alicante, Toulon, Trieste, Dubrovnik, Thessaloniki,İskenderun, Alexandria, Tripoli, Gabès.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation